Numerical study and design of extruded aluminum beams subjected to concentrated loads - Graciano, Carlos; Loaiza, Nelson; Casanova, Euro (Thin-walled structures, 2020)
This paper presents a numerical investigation on the design resistance of extruded aluminum beams subjected to concentrated loads. The study is conducted through nonlinear finite element analysis considering large displacements, initial imperfection, and taking into account the strain hardening characteristics of common aluminum alloys. The numerical model is validated against experimental works taken from the literature. Thereafter, an extensive parametric study is carried out covering a wide range of beam geometries and slenderness ratios. Resistances computed numerically are compared with those calculated using the current design provisions in the EC9 for aluminum beams subject to concentrated loads, indicating that the EC9 provisions underestimate the resistances. Then, a new resistance function is calibrated performing a statistical evaluation of experimental and numerical results. The reliability of the recalibrated resistance function is assessed according to EN 1990, the results show improvements in the predicted resistances. Finally, the use of more accurate structural design provisions enhances the possibility of higher economic benefits, and by using less material, the carbon footprint originated from aluminum production can be reduced. •The patch loading resistance of extruded aluminum beams is analyzed.•An extensive numerical study is performed through GMNIA.•The effect of several geometrical parameters on the resistance are investigated.•A statistical evaluation is conducted to calibrate a new resistance function.